2022
DOI: 10.1002/slct.202103415
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Synthesis of Thioethers through C−N Bond Cleavage of Aminonaphthol/Aminophenol Derivatives

Abstract: Readily available aminonaphthol/aminophenol derivatives were converted to the corresponding thioethers under catalyst‐free reaction conditions. Environmentally benign aqueous medium was utilized for the transformation of aminonaphthol derivatives to the corresponding thioethers under aerobic reaction conditions. Saturated brine solution was identified as a suitable medium for the synthesis of thioethers from aminophenol derivatives. Control experiments revealed that the nature of leaving group and reaction atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Control experiments revealed that the nature of leaving group and reaction atmosphere plays a vital role in determining the yield of the products. 94 Recently, synthesis of 1-[(1S)-(4-uorophenyl)-((1 0 S)-1 0naphthalen-1-yl-ethylamino)-methyl]-naphthalen-2-ol 260 in 79% yield reported by the triation reaction of (S,S)-aminobenzylnaphthol 261 with triuoromethanesulfonic anhydride in the presence of pyridine in dichloromethane at room temperature for 16 h as shown in Scheme 70. Compound 260 can be used as valuable intermediate in the future synthesis of aminophosphine, to be used in asymmetric catalysis.…”
Section: The Other Fused-heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Control experiments revealed that the nature of leaving group and reaction atmosphere plays a vital role in determining the yield of the products. 94 Recently, synthesis of 1-[(1S)-(4-uorophenyl)-((1 0 S)-1 0naphthalen-1-yl-ethylamino)-methyl]-naphthalen-2-ol 260 in 79% yield reported by the triation reaction of (S,S)-aminobenzylnaphthol 261 with triuoromethanesulfonic anhydride in the presence of pyridine in dichloromethane at room temperature for 16 h as shown in Scheme 70. Compound 260 can be used as valuable intermediate in the future synthesis of aminophosphine, to be used in asymmetric catalysis.…”
Section: The Other Fused-heterocyclesmentioning
confidence: 99%
“…Control experiments revealed that the nature of leaving group and reaction atmosphere plays a vital role in determining the yield of the products. 94…”
Section: The Other Reactionsmentioning
confidence: 99%
“…The non‐racemic of the Betti base and Its derivatives could be of special interest for organic chemists working in the field of ligand‐metal catalyzed reaction. It is also clear that the most important area of application of the non‐racemic aminonaphthols is their use in asymmetric transformations, either as chiral ligands or as chiral auxiliaries [19–22] . Also, some of these products possess biological activity [23–28] .…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear that the most important area of application of the non-racemic aminonaphthols is their use in asymmetric transformations, either as chiral ligands or as chiral auxiliaries. [19][20][21][22] Also, some of these products possess biological activity. [23][24][25][26][27][28] However, in spite of the number of structures reported, it is possible to synthesize and investigate applications of the various structures of these compounds due to their importance.…”
Section: Introductionmentioning
confidence: 99%